Search for massive WH resonances decaying into the l nu b(b)over-bar final state at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
A search for a massive resonance W'decaying into a W and a Higgs boson in the l nu b (b) over bar (l = e, mu) final state is presented. Results are based on data corresponding to an integrated luminosity of 19.7 fb(-1) of proton-proton collisions at root s = 8 TeV, collected using the CMS detector at the LHC. For a high-mass (greater than or similar to 1 TeV) resonance, the two bottom quarks coming from the Higgs boson decay are reconstructed as a single jet, which can be tagged by placing requirements on its substructure and flavour. Exclusion limits at 95 % confidence level are set on the production cross section of a narrow resonance decaying into WH, as a function of its mass. In the context of a little Higgs model, a lower limit on the W' mass of 1.4 TeV is set. In a heavy vector triplet model that mimics the properties of composite Higgs models, a lower limit on the W' mass of 1.5 TeV is set. In the context of this model, the results are combined with related searches to obtain a lower limit on the W' mass of 1.8 TeV, the most restrictive to date for decays to a pair of standard model bosons.